Improving Cadence and Walking Speed after Extracorporeal Shockwave Therapy: Preexperimental Study in Knee Osteoarthritis Patients - Amandha Boy Timor Randita; Imam Subadi; Nurul Kusuma Wardani; Ardhi Wicaksono Santoso; Soenarnatalina Melaniani (Biomolecular and Health Science Journal)
Introduction: Current treatment for knee osteoarthritis (KOA) has aimed at inhibiting the degenerative processes of osteoarthritis by regenerative medicine. One of the physical modalities that have a regenerative effect is extracorporeal shockwave therapy (ESWT). There was limited evidence based for evaluating the improvement function of KOA, especially after ESWT management. This study aimed to investigate the effect of ESWT by serial evaluation of cadence and gait speed for patients with KOA.